2017
DOI: 10.26687/archnet-ijar.v11i3.1378
|View full text |Cite
|
Sign up to set email alerts
|

Walkability in Historic Urban Spaces: Testing the Safety and Security in Martyrs' Square in Tripoli

Abstract: Keywords Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 29 publications
1
21
1
2
Order By: Relevance
“…The built environment in emerging countries is ruled by a car-oriented perspective, with a lack of infrastructure for pedestrians, unequal and uncontrolled growth and weak public regulation (Cervero, 2013;Cervero, Sarmiento, Jacoby, Gomez, & Neiman, 2009). People are used to an unfavourable environment for pedestrians, and socioeconomic characteristics, therefore, play an important role in encouraging walking (Abdulla, Abdelmonem, & Selim, 2017;Larrañaga et al, 2014a).…”
Section: Walkability In the Latin American Contextmentioning
confidence: 99%
“…The built environment in emerging countries is ruled by a car-oriented perspective, with a lack of infrastructure for pedestrians, unequal and uncontrolled growth and weak public regulation (Cervero, 2013;Cervero, Sarmiento, Jacoby, Gomez, & Neiman, 2009). People are used to an unfavourable environment for pedestrians, and socioeconomic characteristics, therefore, play an important role in encouraging walking (Abdulla, Abdelmonem, & Selim, 2017;Larrañaga et al, 2014a).…”
Section: Walkability In the Latin American Contextmentioning
confidence: 99%
“…Although there is no consensus on how to analyze the several built environment attributes related to walkability, research has shown that the dimensions of the built environment beneficial for walking trips are the 5Ds density; diversity; design; destination accessibility, and distance to public transport [41]. However, 3Ds (design, diversity and density) are the most common criteria addressed in previous studies and used to construct walkability indexes [1,6,[41][42][43].…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Numerous researchers have reviewed the mixed findings regarding the association between walkability, safety and security demonstrating that walkability is not only associated with the physical environment, but safety and security also play an important role in attracting people to public spaces for walking [4,6,[23][24][25][26][27]. Moreover, it is considered that security should be the foundation for a sustainable city, because with the lack of security, daily activities can become risky.…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 2 more Smart Citations